PRACTICES AND CHALLENGES OF PUBLIC AND PRIVATE PRESCHOOLS OF JIGJIGA CITY ADMINISTRATION - Haile, Yigzaw; Mohammed, Abdirahman (International Journal of Research -GRANTHAALAYAH, 2017)
The main purpose of this study was to assess practices and challenges of preschool education in Jijiga City administration. Mixed design was employed (both quantitative and qualitative) for this study. 19 preschool centres (6 public and 13 private preschools) were randomly selected for the study. 51 preschool teachers (12 teachers from public and 39 teachers from private teacher) were selected. A semi-structured questionnaire was used to collect quantitative data in which 57 items were filled by preschool teachers which are dealing with Early Childhood Care and Education (ECCE) practices. Interview, FGD, observation and document analysis were used to triangulate the data collected using questionnaire. Percentage and thematic analysis were used to analyze the quantitative and qualitative data respectively. The main findings revealed that preschool practices in all sampled preschools were found to be below standard, unable to use local stories since teachers were not from the community and knowledge of parents, teachers and principals towards contribution of the preschool was found to be limited. It was found that 82.4% of the preschool had no early childhood care and education qualification, and 70.6% of the preschool teachers did not agreed that all sampled preschools had inadequate classroom space, 64.7% of the preschool centres did not have age appropriate chairs. Similarly, 76.5 % of the preschool had no any out-door playing material and 100 % of all preschool did not used approved curriculum and lack of appropriate teaching used in most of the preschool were some of the main finding. The Ethiopia Somali Regional Education Bureau is recommended to address shortage of trained ECCE teachers, develop standardized ECCE curriculum, applying developmentally appropriate content, materials, and teaching methods, use locally and culturally appropriate materials and assign teachers who can speak the local language of the community.